2015
DOI: 10.1111/hex.12326
|View full text |Cite
|
Sign up to set email alerts
|

Community preferences in general practice: important factors for choosing a general practitioner

Abstract: Background Understanding the important factors for choosing a general practitioner (GP) can inform the provision of consumer information and contribute to the design of primary care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 22 publications
(62 reference statements)
1
25
0
Order By: Relevance
“…The survey has been described previously, 18 and publications have reported results relating to bulkbilling rates, preferences for care and the quality of general practice services. 14,18,19 The key variable of interest for this study was whether respondents reported attending more than one general practice in the previous 12 months. Explanatory variables relate to respondents' Michael Wright, Jane Hall, Kees van Gool, Marion Haas…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey has been described previously, 18 and publications have reported results relating to bulkbilling rates, preferences for care and the quality of general practice services. 14,18,19 The key variable of interest for this study was whether respondents reported attending more than one general practice in the previous 12 months. Explanatory variables relate to respondents' Michael Wright, Jane Hall, Kees van Gool, Marion Haas…”
Section: Methodsmentioning
confidence: 99%
“…12 Most Australians report having a regular GP, 11,13 and have strong preferences for seeing a GP who knows them. 14,15 However, consultations with multiple GPs are common, 5 and previous research suggests that patients who attend multiple general practices are more likely to be younger, female, have a higher education attainment, and are more frequent users of health services 5,16 than single general practice attenders.…”
Section: Contextmentioning
confidence: 99%
“…Therefore, this data may only be accurate for our group of patients and cannot be understood in the sense that all immigrants in Slovenia have equal opportunities to get an appointment at a GP’s office. The available data from the literature show that the choice of GP is influenced by several different factors, such as care quality, availability, and practice characteristics (33) . Comparable data have been obtained in Canada with respect to the availability of GPs and other specialists for immigrants and for the rest of the population.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothetical practices were described in terms of 10 attributes of a medical practice (Table 1), which were developed based on an earlier study [15] involving a population survey where respondents rated the importance of a list of 36 attributes of general practice identified from a literature review.…”
Section: Choice Experimentsmentioning
confidence: 99%